2019
DOI: 10.1111/jvs.12770
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of past land use and recent forest management on the understorey community in temperate oak forests in South Sweden

Abstract: Questions Past agricultural land use and forest management have shaped and influenced the understorey composition in European forests for centuries. We investigated whether understorey vegetation assemblages are affected by (a) legacies from a historical infield/outland agricultural system (i.e., a system with nutrient‐enriched vs nutrient‐depleted areas), (b) recent management intensity (i.e., thinning/felling activities), and (c) the interaction of recent management and potential legacies. Location Oak fores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 67 publications
0
11
0
1
Order By: Relevance
“…Apart from quantified natural and anthropogenic disturbance effects, a variety of other processes could be directly or indirectly driving these diversity changes at different scales. Local and regional scale drivers, such as ungulate browsing damage [58] and legacies of past land use [59], have been shown to be responsible for detectable changes in understory composition over time [60]. Additionally, environmental factors and disturbance agents operating on larger spatial and longer temporal scales, including large-scale climate change and atmospheric nutrient deposition [7,10] could contribute to plant community dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from quantified natural and anthropogenic disturbance effects, a variety of other processes could be directly or indirectly driving these diversity changes at different scales. Local and regional scale drivers, such as ungulate browsing damage [58] and legacies of past land use [59], have been shown to be responsible for detectable changes in understory composition over time [60]. Additionally, environmental factors and disturbance agents operating on larger spatial and longer temporal scales, including large-scale climate change and atmospheric nutrient deposition [7,10] could contribute to plant community dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Here it grows with species such as Anemone nemorosa, Lathyrus vernus, Mercurialis perennis, Milium effusum and Polygonatum multiflorum. Some of these woodlands were formerly wooded meadows used for grazing or mowing that formed part of medieval infield systems (Depauw et al, 2019). Occasionally, P. nemoralis can occur in boreal herb-rich woodlands (groves), which are more open woodland types, partly due to former slash and burn cultivation (Hokkanen, 2003).…”
Section: Communitie Smentioning
confidence: 99%
“…In a multifactor experiment on herbaceous communities, Blondeel et al (2020) found that light, rather than global‐change drivers (nitrogen deposition and warming) or past land use, determined development trajectories of forest understorey communities over a period of three years. In a resurvey study in temperate oak forests in South Sweden, Depauw et al (2019b) concluded that light dynamics due to management practices play a key role in the development of the understorey composition.…”
Section: Introductionmentioning
confidence: 99%